High-resolution study of the air-sea CO2 flux and net community oxygen production in the Ligurian Sea by a fleet of gliders - Coppola, Laurent; Fourrier, Marine; Pasqueron de Fommervault, Orens; Poteau, Antoine; Riquier, Emilie Diamond; Béguery, Laurent (Frontiers in Marine Science, 2023)
Intense glider monitoring was conducted in the Ligurian Sea for five months to capture the Net Community Production (NCP) variability in one of the most dynamic and productive regions of the Mediterranean Sea. Using the SeaExplorer glider technology, we were able to observe continuously from January to the end of May 2018 the physical and biogeochemical variables during the last period of intense convection observed in this region. High-frequency measurements from these gliders provided valuable information for determining dissolved O2 (DO) concentrations between coastal and open sea waters. Our DO balance approach provided an estimate of NCP fluxes complemented by the prediction of air-sea CO2 fluxes based on a neural network adapted to the Mediterranean Sea (CANYON-MED). Based on our NCP calculation method, our results show that the air-sea O2 flux and DO inventory have contributed largely to the NCP variability. The NCP values also suggest that heterotrophic conditions were predominant in winter and became autotrophic in spring, with strong variability in coastal waters due to the occurrence of sub-mesoscale structures. Finally, CO2 fluxes at the air-sea interface reveal that during the convection period, the central zone of the Ligurian Sea acted as a CO2 sink from January to March with little impact on NCP fluxes counterbalanced by a thermal effect of seawater.